The effect of Ixodes ricinus tick serpin on the cytotoxic function of natural killer cells - Fišerová, Simona (Jihočeská univerzita, 2020)
The aim of my thesis was the functional characterization of IRS-4 from Ixodes Ricinus. Particularly the effect of IRS-4 on cytotoxic activity of NK cells was analysed. First, the optimization of calcein-AM release method, which was used for this analysis, was performed. Afterwards, the method was used for the measurement of the cytotoxic activity of NK cells. Moreover, the effect of tick serpin on the activation of NK cells by measuring the cytokine production IFN- was examined.
The effect of Ixodes ricinus tick serpin on the cytotoxic function of natural killer cells
Keywords: IRS-4; serpins; natural killer cells (NK); NK cytotoxicity; calcein-AM; IRS-4; serpins; natural killer cells (NK); NK cytotoxicity; calcein-AM